Carbon neutral drying technologies for sustainable transformation in Thailand's rubber industry - Kyu Kyu Tin; Anil Kumar (Sustainable Futures)
In Thailand, rubber drying process is transitioning towards more sustainable best practices, with a strong emphasis on minimizing environmental impact. Therefore, this review intends to elevate the effectiveness of microwave drying technology powered by solar energy in reducing carbon dioxide emissions than traditional hot air drying applying liquefied petroleum gas (LPG). Moreover, it includes a comparative analysis of drying technologies, focusing on energy consumption, emission levels, and product quality. Microwave drying has the potential to eliminate up to 300,000 tons of carbon dioxide annually in the Standard Thai Rubber (STR) drying industry. Plus, major rubber producers in Thailand, such Sri Agro and Southland Rubber Industry, are spearheading sustainability initiatives by setting ambitious targets for carbon neutrality, emission reduction, and net zero goals. These companies are also investing in supply chain traceability and supplier engagement to elevate sustainable best practices. Besides, research into hybrid solar-biomass drying systems for para rubber sheets has promising results, helping efficient drying with high quality and lower costs compared to traditional techniques like sun exposure or smoke drying. Following these insights, recommends broader industry adoption of microwave and hybrid drying technologies, alongside policy incentives to support sustainable transformations. As a global leader in sustainable manufacturing, these innovative approaches underscore Thailand’s commitment to fostering environmentally friendly rubber processing methods and positioning the industry.